Structure-Function Studies of the Self-Assembly Domain of the Human Immunodeficiency Virus Type 1 Transmembrane Protein gp41 - Weng, Yongkai (American Society for Microbiology, 2000)
The coiled-coil region of the human immunodeficiency virus type 1 transmembrane protein (gp41) makes up the interior core of the six-helix bundle structure of the gp41 self-assembly domain. We extended our previous study of this domain (Y. Weng and C. D. Weiss, J. Virol. 72:9676–9682, 1998) by analyzing 23 additional mutants at positions that lie at the interface of the interior core and outer helices. We found nine new functional mutants. For most mutants, the activity could be explained by the ability of the modeled mutants to stabilize the six-helix bundle structure. The present study provides insights into the envelope glycoprotein fusion mechanism and information for rational drug and vaccine design.